The Roles of Financial Knowledge, Motivation and Self Efficacy on the Influence of Financial Education toward Financial Literacy - Thomas, Partono; Mulyono, Kemal Budi; Setiaji, Khasan (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to know the influence of financial education toward financial literacy on Economics Faculty students. In Economics Faculty, Universitas Negeri Semarang, there were 16 of 40 students who had good financial behaviors. It was contradictive because they have taken accounting subject who make them good in financial literacy. The research on financial literacy had the contradiction, especially in the influence of financial education variable on financial literacy. Therefore, this study raised the mediating variables; the consumer knowledge variable and psychological factor variables (motivation, self efficacy). This study was analyzed by two analyses that were descriptive analysis and path inferential analysis. Findings show that students’ financial literacy and financial education are in enough categories; whereas, motivation and self-efficacy are in good condition, and students’ financial knowledge is in unfavorable category. The results of path analysis show that the variable of financial education does not have any direct influence toward financial literacy, but it has indirect influence through motivation. Then, the variable of financial education also does not have any direct influence toward self-efficacy, and self-efficacy does not influence toward financial literacy and financial knowledge does not have any influence toward financial literacy. Thus; the learning process on Finance should involve three aspects; cognitive, affective, and psychomotor; and it needs the development of learning model on Finance to involve students’ activeness in managing their financial activities.